The potential development of oxygen optical fibre gas sensor for automotive industry - A. R., Zul Rasyied; N. N., Mazlee; M. R., Salim; Hadi, Manap; S., Nurulain (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
This paper describes the potential future development of an optical fibre based sensor for oxygen detection in the UV region between 200-230 nm. An open-path optical method is used to analyze the absorption lines of the oxygen in the UV region. Experimental result describing the operation of the sensor is presented. A comparison between theoretical and experimental results has been carried out and reported.